2018
DOI: 10.1016/j.dental.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biofilm formation on novel copper-catalyzed azide-alkyne cycloaddition (CuAAC)-based resins for dental restoratives

Abstract: CuAAC-based resins do still allow for the formation of biofilms; however, the statistically significant reduction of growth that was associated with the CuAAC resin may enhance the longevity of restorations that incorporate CuAAC-based materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 87 publications
0
11
0
1
Order By: Relevance
“…The use of copper in resin composite was attempted to reduce the shrinkage stress of the resin matrix. Photo-initiated copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) polymerization demonstrates three times lower shrinkage stress and more antibacterial activities against S. mutans compared to control restorative polymers [ 78 , 79 ].…”
Section: Bioactivity For Clinical Restorative Polymer Materialsmentioning
confidence: 99%
“…The use of copper in resin composite was attempted to reduce the shrinkage stress of the resin matrix. Photo-initiated copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) polymerization demonstrates three times lower shrinkage stress and more antibacterial activities against S. mutans compared to control restorative polymers [ 78 , 79 ].…”
Section: Bioactivity For Clinical Restorative Polymer Materialsmentioning
confidence: 99%
“…Biofilms were formed with a monospecies biofilm model containing a luciferase-expressing Streptococcus mutans (Zajdowicz et al 2018). Briefly, composite discs 7 mm in diameter and 1 mm thickness were sterilized in 70% alcohol containing 0.5% triclosan for 30 min; 3 experiments were conducted with 3 discs for each sample, yielding a total 9 discs per sample.…”
Section: Methodsmentioning
confidence: 99%
“…The resins used in dental restoration may favor biofilm development and consequently increase the occurrence of secondary caries [ 111 ]. Therefore, copper has been incorporated in resins used for dental restoration.…”
Section: Copper Surfaces In Health Care Unitsmentioning
confidence: 99%
“…Therefore, copper has been incorporated in resins used for dental restoration. Zajdowicz, et al [ 111 ] synthesized a novel copper-catalyzed azide-alkyne cycloaddition (CuAAC) based resins and composites and found that CuACC reduced biofilm formation, protecting dental restorations for longer periods in comparison to other commonly used resins [ 111 ].…”
Section: Copper Surfaces In Health Care Unitsmentioning
confidence: 99%